STRATEGI KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN KINERJA DAN KESEJAHTERAAN GURU DI MI PAS BAITUL QUR’AN GONTOR PONOROGO - Zulfa Nailatul Husna (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2022)
The role of teacher performance is very important in improving the quality of education. This is because the teacher is the main character who interacts directly with students. One of the factors supporting teacher performance lies in the welfare of teachers. Therefore, to improve the quality of education, madrasah principals must be able to manage and develop the performance and welfare of teachers as an effort to improve the quality of education. This study aims to determine the performance and welfare of teachers at MI PAS Baitul Qur'an Gontor Ponorogo and how the headmaster's strategy to improve it. This study uses a descriptive qualitative approach. Data obtained from interviews, observations, and documentation. The results showed that (1) in addition to teaching ability, teacher performance was seen from the teacher's activity in participating in training and committees (2) teacher welfare was divided into two types, namely material welfare in the form of fulfilling life needs and non-material welfare in the form of a sense of kinship, blessing, and development opportunities. themselves through training and committees (3) the leadership strategy of the head of the madrasa is implemented through working meetings, regeneration systems, supervision, value sessions, cooperation, welfare improvement, assignment of tasks and responsibilities and inculcation of the concept of blessing. Abstrak Peran kinerja guru sangatlah penting dalam meningkatkan kualitas pendidikan. Hal ini karena guru merupakan sosok tokoh utama yang berinteraksi langsung dengan peserta didik. Salah satu faktor penunjang kinerja guru terletak pada kesejahteraan guru. Oleh karenanya untuk meningkatkan kualitas pendidikan, kepala madrasah harus mampu mengelola dan mengembangkan kinerja serta kesejahteraan guru sebagai upaya meningkatkan kualitas pendidikan. Penelitian ini bertujuan untuk mengetahui kinerja dan kesejahteraan guru di MI PAS Baitul Qur’an Gontor Ponorogo serta bagaimana strategi kepala madrasah untuk meningkatkannya. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Data diperoleh dari wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukan bahwa (1) selain kemampuan mengajar kinerja guru dilihat dari keaktifan guru dalam mengikuti pelatihan dan kepanitiaan (2) kesejahteraan guru dibagi menjadi dua jenis yaitu kesejahteraan materi berupa pemenuhan kebutuhan hidup dan kesejahteraan non materi berupa rasa kekeluargaan, keberkahan, serta kesempatan pengembangan diri melalui pelatihan dan kepanitiaan (3) strategi kepemimpinan kepala madrasah diterapkan melalui raker, sistem kaderisasi, supervisi, sidang nilai, kerja sama, peningkatan kesejahteraan, pemberian tugas dan tanggung jawab dan penanaman konsep keberkahan.